PEMBELAJARAN BAHASA DAERAH BALI PADA SISWA DWIBAHASA KELAS VII SLTP DI SEKOLAH HIGH SCOPE INDONESIA-BALI - Dewi, Ni Nyoman Astiti; Suparwa, I Nyoman; Malini, Ni Luh Komang Seri (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2016)
The type of this research is a descriptive qualitative field research. The objects of this research were Balinese language teachers, twelve students grade VIIA, and fourteen students grade VIIB. Descriptive qualitative research method was used in this research. All data were in the form of qualitative and reported through descriptive qualitative and quantitative method was only used for describing the percentage of data in the form of table or graphs. In this research the techniques of data collection were observation, interview, recording, and questionnaires. In collecting the data, there were supporting instruments used they were anecdotal note, interview guidelines and observation guidelines. The data of this research were analyzed by using relevant theories which have close relation with this research such as theory from Asrori, (2007: 125). For the second discussion about the obstacles on learning language a theory from Ovanda & Callier (1985) via (Sudiarta, 2005: 27). was also used. While for the discussion of learning approach HighScope (plan, do and review) by Morrison (2008: 156) was also became an important concern. The result of this research that there were factors such as willingness; motivation and the ability in Balinese language were found while for the external factors covering social school environment, and family. There was also important thing found such as the instrument of learning language as nonsocial factor. For the obstacles of learning Balinese language, phonology, morphology, syntax and semantics were found as serious problems. Furthermore, the obstacles also came from non language factors such as the origin, mother tongue, gender, and the age of students. The method of Balinese language learning used was the HighScope approach (plan, do and review) which was used to help bilingual students in learning Balinese language.
Keywords: balinese language, learning, students, bilingual.